2021
DOI: 10.3389/fpls.2021.650471
|View full text |Cite
|
Sign up to set email alerts
|

The Spectral Irradiance, Growth, Photosynthetic Characteristics, Antioxidant System, and Nutritional Status of Green Onion (Allium fistulosum L.) Grown Under Different Photo-Selective Nets

Abstract: The active regulation of the plant growth environment is a common method for optimizing plant yield and quality. In horticulture today, light quality control is carried out using photo-selective nets or membranes to improve the yield and quality of cultivated plants. In the present study, with natural light as the control (CK), we tested different photo-selective nets (white, WN; blue, BN; green, GN; yellow, YN; and red, RN) with 30% shade for characteristics of growth, development, quality, yield, photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…W. ugandensis crude extract obtained from the stem bark and leaf using different organic solvents may have had a synergistic effect by stimulating tomato plants' growth through decreased retarding effect of R. solanacearum. These results concur with those of [63,64] Gao et al, (2021 [1]) and [1] Marey & Elmasry, (2024) that treatment of tomato plants with A. fistulosum crude extract increased the height of tomato plants.…”
Section: The Effect Of Soil Treatment With W Ugandensis Crude Extract...supporting
confidence: 91%
“…W. ugandensis crude extract obtained from the stem bark and leaf using different organic solvents may have had a synergistic effect by stimulating tomato plants' growth through decreased retarding effect of R. solanacearum. These results concur with those of [63,64] Gao et al, (2021 [1]) and [1] Marey & Elmasry, (2024) that treatment of tomato plants with A. fistulosum crude extract increased the height of tomato plants.…”
Section: The Effect Of Soil Treatment With W Ugandensis Crude Extract...supporting
confidence: 91%
“…However, different growing environments significantly affect the quality of plants (vegetables or herbs) ( Gao et al, 2021 ). In particular, the average annual temperature in different regions of Shanxi Province increases from the north to the south and decreases from the basins to the high mountains ( Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that MDA content increased with high‐temperature stress, indicating that oxidative damage to green onions increased under high‐temperature stress, which was more evident in thermosensitive green onions. In addition, the antioxidant enzyme system could respond according to the degree of stress to which the plant is subjected (Gao et al 2021). This study showed that with the increase of high‐temperature stress time, the activities of SOD and POD in green onion plants increased, and the enzyme content in the heat‐tolerant variety was lower than that of the heat‐sensitive variety at the same period, which was consistent with other studies (Guo et al 2020, Sattar et al 2020, Su et al 2022).…”
Section: Discussionmentioning
confidence: 99%